2009
DOI: 10.1086/603613
|View full text |Cite
|
Sign up to set email alerts
|

Ecology Predicts Levels of Genetic Differentiation in Neotropical Birds

Abstract: Despite the theoretical link between the ecology and the population genetics of species, little empirical evidence is available that corroborates the association. Here, we examined genetic variation in 40 codistributed species of lowland Neotropical rain forest birds that have populations isolated on either side of the Andes, the Amazon River, and the Madeira River. We found widely varying levels of genetic divergence among these taxa across the same biogeographic barriers. Our investigation of the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
230
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(261 citation statements)
references
References 98 publications
24
230
2
5
Order By: Relevance
“…This result is consistent with population-level studies, which have found a negative association between gene flow and genetic differentiation [2,32,51]. Although range expansion certainly plays an important role in diversification [6], the potentially stimulating effects of colonization and range expansion [7,52] may have been overshadowed by the inhibitory effect of increased levels of gene flow in the Furnariidae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is consistent with population-level studies, which have found a negative association between gene flow and genetic differentiation [2,32,51]. Although range expansion certainly plays an important role in diversification [6], the potentially stimulating effects of colonization and range expansion [7,52] may have been overshadowed by the inhibitory effect of increased levels of gene flow in the Furnariidae.…”
Section: Discussionsupporting
confidence: 87%
“…Empirical evidence supports the hand-wing index as a valid surrogate for flight and dispersal ability in birds. Flight performance (see the electronic supplementary material), migratory behaviour [29,30], natal dispersal distance [31] and genetic differentiation [32] are all correlated with this index. Because the index varies on a continuous scale, it can be used to study higher order relationships between dispersal and diversification like the intermediate dispersal model.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, we show that differences in intrinsic dispersal potential provide the best explanation for the failure of many terrestrial vertebrate species to attain sympatry even millions of years after speciation. This makes sense because barriers to dispersal in terrestrial systems have extremely protracted effects that vary according to dispersal limitation, for example when rivers, mountain ranges or narrow regions of unsuitable climate and vegetation cause longstanding disjunctions in the geographical ranges of sister species in lineages with low dispersal ability, but not those with high dispersal ability [19,45,48].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the higher number of habitat strata in lowland tropical forest may allow vertical segregation of ecological competitors with similar traits, facilitating coexistence without direct contact [6,27]. However, because ecological adaptations to different vegetation strata are also associated with consistent biometric differences in traits such as tarsus or wing length [25,42], we expect that these effects should also be detected in our analyses.…”
Section: H M H M Hmentioning
confidence: 96%